2017
DOI: 10.1186/s40349-017-0080-4
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of palliative treatment of pancreatic cancer with high intensity focused ultrasound

Abstract: BackgroundPancreatic adenocarcinoma is currently the fourth-leading cause of cancer-related death. Up to 60–90% of patients with advanced disease suffer cancer-related pain, severely impacting their quality of life. Current management involves primarily pharmacotherapy with opioid narcotics and celiac plexus neurolysis; unfortunately, both approaches offer transient relief and cause undesired side-effects. High intensity focused ultrasound (HIFU) is a non-invasive thermal ablation technique that has been used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 54 publications
(63 reference statements)
2
47
1
Order By: Relevance
“…It was first reported in 2000 that HIFU successfully ablates and treats pancreatic cancer (29). Several studies have confirmed the safety and efficacy of HIFU in the treatment of pancreatic cancer (10,(14)(15)(16)(19)(20)(21)(22)(23)(24)(25)(29)(30)(31)(32)(33)(34). The most common complications observed following HIFU treatment of pancreatic cancer include skin burns (10,15,17,(21)(22)(23)(30)(31)(32), pancreatitis (10,18,23,31,32), duodenal fistula (23,31) and obstructive jaundice (19,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was first reported in 2000 that HIFU successfully ablates and treats pancreatic cancer (29). Several studies have confirmed the safety and efficacy of HIFU in the treatment of pancreatic cancer (10,(14)(15)(16)(19)(20)(21)(22)(23)(24)(25)(29)(30)(31)(32)(33)(34). The most common complications observed following HIFU treatment of pancreatic cancer include skin burns (10,15,17,(21)(22)(23)(30)(31)(32), pancreatitis (10,18,23,31,32), duodenal fistula (23,31) and obstructive jaundice (19,34).…”
Section: Discussionmentioning
confidence: 99%
“…widely used in the treatment of uterine fibroids and hepatocellular carcinoma, with good therapeutic results (12). Previous studies have confirmed that HIFU therapy effectively alleviates cancer-associated abdominal pain, reduces tumor volume and may confer an additional survival benefit (11,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). However, vascular complications caused by this treatment have been reported, including secondary occlusion of the superior mesenteric artery (24) and portal vein thrombosis (25).…”
Section: Effects Of High-intensity Focused Ultrasound Treatment On Pementioning
confidence: 99%
“…[21][22][23][24][25] Results from a meta-analysis showed that approximately 80% of patients with advanced PC who received HIFU therapy experienced pain reduction. 26 Ji et al 27 also reported that HIFU treatment was effective and the adverse events (AEs) associated with the treatment were rare and tolerable, especially for old patients and those with poor performance status. 28 Our previous study was also consistent with these results.…”
Section: Discussionmentioning
confidence: 99%
“…Typical study endpoints have included safety and feasibility confirmation, tumor volume reduction, and pain relief [104110]. A comprehensive review of all clinical treatment series employing palliative FUS therapy for pancreatic cancer treatment is beyond the scope of this paper; but we direct the reader to an excellent recent meta-analysis by Dababou et a l that examined 23 studies on this topic and showed an overall pain reduction in 81% of treated patients (95% CI: 76–86) [111]. A recent, moderately powered (n=689) retrospective analysis from China revealed an independent median overall survival benefit from ablative FUS treatment for patients with unresectable PDA who also received a variety of multi-modal treatment regimens, without severe adverse events (7.1 versus 5 months; p=0.005) [112].…”
Section: Introductionmentioning
confidence: 99%